Choosing a Virtual Learning Environment for the University of Bristol - Bayne, Siân; Cook, Julian; O'Leary, Ros (Proceedings of the International Conference on Networked Learning, 2000)
We are currently exploring the potential of, and practicalities involved in, the implementation of networked learning tools across the University of Bristol. Our project is to ascertain first the readiness of the institution for such an implementation and second, the form such an implementation should take.